Storm eaudiobook - Kemmerer, Brigid (Elemental, 2015)
Ever since her ex-boyfriend spread lies about her, Becca Chandler is suddenly getting all the guys—the ones she doesn't want. Then she saves Chris Merrick from a beating in the school parking lot. Chris is different. Way different: he can control water—just like his brothers can control fire, wind, and earth. They're powerful. Dangerous. Marked for death. And now that she knows the truth, so is Becca. When Hunter, the mysterious new kid in town, turns up with a talent for being in the wrong place at the right time, Becca thinks she can trust him. But then Hunter goes head-to-head with Chris, and Becca wonders who's hiding the most dangerous truth of all . . .